Innovative Solutions and Performance Assessment of Green Roofs - Materials, Technology Aspects and Building Passive Cooling - Cascone, Stefano (Innovative Solutions and Performance Assessment of Green Roofs - Materials, Technology Aspects and Building Passive Cooling, 2022)
Over the past half century, building and city models adopted are not practicable and usable anymore, since they have been built with a disregard of nature and, therefore, it is important to find solutions to adapt or to mitigate the effects of higher temperatures and to address urban challenges. The building sector typically contributes to at least 30–40% of both energy consumption and carbon emissions in most countries. Designing sustainable energy-efficient buildings is the main goal of world environmental policies for reducing the carbon footprint from the building sector. This context calls for zero-impact or at least low-impact technical solutions in conceiving the building envelope. Since most cities show space constraints, in the general field of green infrastructures, green roofs could play a major role because, in addition to the several social, economic, public health, and environmental benefits, they can help to improve building thermal performance, especially in summer, and to optimize urban stormwater management. Nonetheless, some limits still affect the energy modeling and environmental and economic analyses of these components and green roofs must be adapted to local conditions and included in urban green infrastructure plans to mitigate climate change. The objectives of the Monograph were achieved through both numerical analysis and experimental research that are summarized in the following list: To identify substrate-vegetation combinations that determine the highest thermal performance in the Mediterranean climate. To determine the performance of green roofs used for the retrofitting of existing To propose an innovative green roof using low-density polyethylene (LDPE) granules as drainage layer. To validate an innovative set-up for the evaluation of evaporative cooling due to extensive green roofs at the University of Lleida and to correlate the evaporation process with the thermal performance of the green roof. This Monograph will contribute to evaluate the best solutions for green roofs within the scope of the resilience and climate adaptation strategies needed for cities and passing on this information to decision makers. The Monograph is divided into 5 chapters. In Chapter 1 the problem is presented and in Chapter 2 the literature is analyzed in order to identify the technology and materials used in green roofs. The other chapters represent the proposal phase of the book where numerical analyses (Chapter 3) and experimental evaluations (chapters 4 and 5) are described. In Chapters 3, the performance of different green roof configurations is determined, also for the retrofitting existing buildings. In Chapter 4. an innovative technology using recycled polyethylene granules as drainage layer is proposed. Finally, in Chapter 5, an innovative set-up was designed, built and validated to determine the evapotraspirative cooling of green roofs. The Monograph is developed from my PhD thesis. I am the only author of the thesis. In addition, I obtained the permission to publish it from my tutor prof. Gaetano Sciuto (University of Catania) and the other researchers that collaborated with me in developing the thesis, such as prof. Antonio Gagliano (University of Catania) and prof. Tiziana Poli (Politecnico di Milano).